Strengthening Inclusive Ownership through Capacity Development : Operational Lessons from Case Studies - Balbo Di Vinadio, Tommaso; Sinha, Priyanka; Sachdeva, Paramjit (World Bank, Washington, DC, 2015)
Ownership of development goals and priorities by local stakeholders is widely viewed as a critical factor impacting development effectiveness and achievement of the Millennium Development Goals (MDGs). The 2008 Accra Agenda for Action identifies the concept as one of inclusive ownership, involving parliaments, local authorities and civil society organizations (CSOs), as well as governments. The importance and challenges of building such broad-based ownership across society were a key discussion topic at the Fourth High Level Forum on Aid Effectiveness in November 2011 at Busan. This study aims to generate deeper operational knowledge on what can be done to foster inclusive ownership; its initial findings were presented at Busan. This study involves a retrospective review of a small sample of cases. From these cases it is possible to demonstrate that inclusive ownership, when considered in terms of the operational dimensions examined in the study, can improve as a result of strategic capacity development efforts. It also shows how using an analytic lens such as the CDRF, in particular for the assessment of intermediate results of capacity development, helps to deconstruct the change process in a given case and suggest some operational lessons. Further learning is warranted on how inclusive ownership can be fostered through the design and delivery of capacity development initiatives. Collaboration among and across global communities concerned with ownership and capacity development would enable this work to draw on wider development experiences and generate deeper knowledge on how capacity development can support transformative change.